Impacts of the covid-19 pandemic under the aid of the consumer defense code (Research, Society and Development, 2020)
The main content of this article is to analyze, using the State of São Paulo as a parameter, the socioeconomic impacts resulting from the pandemic of the new coronavirus (Covid-19), especially with regard to abusive practices that occurred during this period, offering as the normative statements based on free initiative and consumer protection. In this perspective, this article, through exploratory research, of qualitative nature, inductive method, collection of documentary and bibliographic data, proceeded in order to carry out a legal analysis of arbitrary and unjust cause increases in product prices, in light of 1988 Federal Constitution, as well as the Consumer Protection Code. However, it also elucidated the main inconsistencies regarding the violation of the principle of consumer protection. Finally, in view of the exposed problem, it was sought, based not only on the aforementioned principle, but also on proportionality and reasonableness, to clarify the need of the State, based on consumer protection and respect for free initiative, to outline mechanisms capable of preserving and to harmonize both principles, in view of the substantial inconveniences caused to the Democratic Rule of Law by the non-observance of these guarantees.